2019
DOI: 10.1093/intimm/dxz068
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous subsets of B-lineage regulatory cells (Breg cells)

Abstract: B cells represent a key cellular component of humoral immunity. Besides antigen presentation and antibody production, B cells also play a role in immune regulation and induction of tolerance through several mechanisms. Our understanding of B-lineage cells with regulatory ability has been revolutionized by the delineation of heterogeneous subsets of these cells. Specific environmental signals may further determine the polarization and function of B-lineage regulatory cells. With the availability of new genetic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 95 publications
0
34
0
Order By: Relevance
“…Indeed, Tregs have been shown to act in synergy with Bregs to promote immune tolerance. Bregs compose a specific B cell subtype that produces the anti-inflammatory cytokines IL-10 and/or IL-35 ( 38 41 ). They have been found to synthesize allergen-specific IgG4 in AIT treated patients ( 42 , 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Tregs have been shown to act in synergy with Bregs to promote immune tolerance. Bregs compose a specific B cell subtype that produces the anti-inflammatory cytokines IL-10 and/or IL-35 ( 38 41 ). They have been found to synthesize allergen-specific IgG4 in AIT treated patients ( 42 , 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the interleukin-10 (IL-10)-producing CD1d + Bregs were induced in a chronic inflammatory environment and dampened the progression of intestinal inflammation by repressing inflammatory cascades associated with IL-1 upregulation and STAT3 activation. Thereafter, mounting evidence has uncovered the roles of Bregs in numerous diseases and conditions, such as infection (16), allergies (17), autoimmune diseases (18), transplantation (19), and tumors (20).…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena are the result of the infiltration of lymphocytes into the synovium and the production of collagen-specific IgG autoantibodies by B cells (4). Recently, a new subset of B cells termed regulatory B cells (Breg cells) were identified that can secrete interleukin-10 (IL-10) to inhibit the production of proinflammatory cytokines and restrain excessive immune responses (5,6). The adoptive transfer of Breg cells has been reported to suppress the development of arthritis (7).…”
Section: Introductionmentioning
confidence: 99%